2021
DOI: 10.3389/fmed.2021.744141
|View full text |Cite
|
Sign up to set email alerts
|

Removal of COVID-19 Spike Protein, Whole Virus, Exosomes, and Exosomal MicroRNAs by the Hemopurifier® Lectin-Affinity Cartridge in Critically Ill Patients With COVID-19 Infection

Abstract: Coronavirus−19 (COVID-19) has rapidly spread throughout the world resulting in a significant amount of morbidity and mortality. Despite advances in therapy, social distancing, masks, and vaccination many places in the world continue to see an increase in the number of cases and deaths. Viremia is commonly present in severely ill patients with COVID-19 infections and is associated with organ dysfunction and poor outcomes. Exosomes released by activated cells have been implicated in the pathogenesis of COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Some variability was observed with the greatest binding observed for the Brazilian P.1 variant and current Omicron variant and the lowest observed for the Delta variant AY.1 ("Delta Plus"). This data correlates with the in vivo data with the adult Hemopurifier where a COVID-19 patient experienced a 58% reduction in plasma viral load following a single 6-hour treatment [4].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Some variability was observed with the greatest binding observed for the Brazilian P.1 variant and current Omicron variant and the lowest observed for the Delta variant AY.1 ("Delta Plus"). This data correlates with the in vivo data with the adult Hemopurifier where a COVID-19 patient experienced a 58% reduction in plasma viral load following a single 6-hour treatment [4].…”
Section: Discussionsupporting
confidence: 82%
“…The Aethlon Hemopurifier® device contains an affinity resin containing Galanthus nivalis agglutinin (GNA) that binds to alpha 1,3 mannose groups in enveloped viruses [ 3 ]. It has been previously demonstrated that the Aethlon Hemopurifier®, an extracorporeal device that contains the GNA affinity resin, binds and removes SARS-CoV-2 from the circulation in vivo [ 4 ]. As the mutations in the SARS-CoV-2 should not affect mannosylation in the viral envelope, we hypothesized that the GNA affinity resin should have similar binding to the major variants causing clinical disease over the past two years.…”
Section: Introductionmentioning
confidence: 99%
“…This adsorbent protein is bound to the extra-capillary space of the filter, where pathogen is immobilized after filtration through 200-nm pores. Data to support the use of Hemopurifier are currently limited to in vitro studies; small safety studies; and case reports in patients with hepatitis C, Ebola, and COVID-19 [165][166][167][168]. A planned prospective trial (NCT04595903) in COVID-19 patients was recently terminated due to inadequate enrollment.…”
Section: Proceedings Of the 2022 Crrt Academymentioning
confidence: 99%
“…The effects of plant lectins on other pathogenic enveloped viruses have been more scarcely investigated. Plant lectins were identified as blocking agents for the entry of IV [45,52,57], HSV [57], HCMV [47,53,54], EBOV [47,48], LASV [47], and the coronaviruses MERS-CoV [51], SARS-CoV [42,51,54,62,63,104], and SARS-CoV-2 [50][51][52]58,60,61,66] in their corresponding host cells. However, depending on the viruses, the envelope glycoprotein(s) targeted by plant lectins are extremely diverse as mentioned in Table 2.…”
Section: How Can the Infectivity Of Pathogenic Enveloped Viruses Be Affected By Lectins?mentioning
confidence: 99%